Pembibitan Tanaman Purwoceng (Pimpinella pruatjan Molk) dengan Abu Vulkanik - Sudrajad, Heru; Suharto, .; Fauzi, . (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2015)
Purwoceng (Pimpinella pruatjan Molk) represents one of the plantation medicines of Indonesia, which its population was almost extinction (endangered). Purwoceng represent the original plant of Indonesia with the swampy forest limited so that need special effort to preserve. Purwoceng represents the endemic species which was growing in the mountain with the height of 1.800-3.500 m dpl in West Java (Pangrango Mountain), Central Java (Dieng plateau) and East Java. Purwoceng seeds represent the highly cost commodity, which is observed by a lot of jamu industry. Volcano dusty from Kelud mountain eruption on Thusday, 12 February 2014 diseminating widely and reach the region Yogyakarta, Central Java and West Java. The volcano dusty could give the fertility of land and plant. It became the good materials for media planting. This research was conducted in Medicinal Plant and Traditional Medicine Research and Development Centre with Complete Random Device Methods, by using the volcano dusty media of Kelud mountain with the treatment of giberelin 0 (control), 25, 50 and 75 ppm. The research showed that the purwoceng seed with the addition of giberelin 25 ppm gave the best result of growth, the average of total leaf was 6,7 pieces, the length of handle was 6,11 cm and the length of root was 11, 7 cm with the colour of leaf was yellow green at 3 month olds.